PENEGAKAN HUKUM TERHADAP APARAT KEPOLISIAN YANG LALAI MENYIMPAN SENJATA API SEHINGGA MENGAKIBATKAN DISALAHGUNAKAN OLEH ORANG LAIN (Studi Kasus Laporan Polisi: LP-A/87/XII/HUK.12.10/2018 TGL 17 Desember 2018) - Klaran, Adriano Y; Medan, Karolus Kopong; Manuain, Orpa G (Petitum Law Journal, 2023)
In accordance with LP-A/87/XII/HUK.12.10/2018 DATE 17 December 2018, the sanctions given are in the form of a written warning, postponement of attending education for a maximum of 1 (one) year, transfer in the nature of demotion, release from position and placement in the case no later than 21 (twenty one) days, the sanctions are given in accordance with Government Regulation Law Number 2 of 2003 article 9 letters (a, b, e, f and g) of the Indonesian National Police concerning Disciplinary Regulations for Members of the Indonesian National Police . Factors that cause police officers to commit negligence regarding firearms are environmental factors which have an impact on the psychological and emotional condition of the police themselves, lack of knowledge and lack of professionalism of the police in carrying out their duties, lack of discipline and lack of adequate training which results in this occurrence. this negligence. The efforts made are preventive efforts, namely preventive efforts by paying attention to and tightening the requirements before providing firearms by members of the Police. Carry out the requirements for the use of firearms by police officers, including; granting permits through an examination mechanism for apparatus, taking into account mentality, professionalism, proportionality, as well as more intensive training.